2005
DOI: 10.1002/ijc.21399
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Cdk4 expression in microsatellite unstable colon cancers with TGFBR2 mutations

Abstract: Approximately 15% of human colon cancers have microsatellite instability (MSI) and carry frameshift mutations in a polyadenine tract (BAT-RII) in the type II transforming growth factor b (TGFb) receptor (TGFBR2), a required component of the TGF-b receptor. The BAT-RII mutations in MSI colon cancers make the tumors resistant to the effects of TGF-b. In cultured epithelial cells, TGF-b can inhibit cell proliferation and induce apoptosis, and in vitro it can regulate the expression of a variety of cyclins, cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 53 publications
(66 reference statements)
1
21
0
Order By: Relevance
“…Tgfβ signaling is known to play important roles in differentiation, cell motility, cell cycle, apoptosis, and inflammation (11), is critical during several phases of mammalian development (12)(13)(14), and is altered in cancer (15,16). Tgfβ signaling involves Tgfβ ligands (Tgfβ1, 2, or 3) that bind to and activate Tgfβ receptors on the cell surface.…”
mentioning
confidence: 99%
“…Tgfβ signaling is known to play important roles in differentiation, cell motility, cell cycle, apoptosis, and inflammation (11), is critical during several phases of mammalian development (12)(13)(14), and is altered in cancer (15,16). Tgfβ signaling involves Tgfβ ligands (Tgfβ1, 2, or 3) that bind to and activate Tgfβ receptors on the cell surface.…”
mentioning
confidence: 99%
“…In addition, previous studies have not shown any correlation for p27 expression with MSI status 23 or mutations in the TGFBR2 gene (encoding TGF-b receptor type II) within MSI-H tumors. 24 In this study, using quantitative real-time PCR (MethyLight) assays, 19,[25][26][27] and population-based samples of colorectal cancer from two large prospective cohort studies, we have shown correlations of loss of nuclear p27 expression with CIMP and MSI. MethyLight assays can reliably distinguish high from low levels of DNA methylation, the latter of which likely have little or no biological significance.…”
mentioning
confidence: 99%
“…Moreover, oncodomain hotspots are able to identify genes that are known to be associated with particular cancer types where traditional methods may fail. For example the seven genes identified by oncodomain hotspots for COAD ( ERBB2 [109,110], EGFR [111,112], KIT [113,114], BRAF [115117], RET [118,119], CDK4 [120122], ALK [123125], and MAPK1 [126128]) are reported to have been involved with COAD. Interestingly, all of these genes were found to be mutated in only six or fewer patients with the exception of BRAF , which was mutated in 32 patients but was still not identified by MutSigCV or CHASM in S2 Fig.…”
Section: Discussionmentioning
confidence: 99%